Coercive parenting: modifiable and nonmodifiable risk factors in parents of children with developmental disabilities. Issue 4 (28th January 2021) - Day, J. J.; Hodges, J.; Mazzucchelli, T. G.; Sofronoff, K.; Sanders, M. R.; Einfeld, S.; Tonge, B.; Gray, K. M.; ,
Abstract: Background: Parents of children with developmental or intellectual disabilities tend to report greater use of coercive parenting practices relative to parents of typically developing children, increasing the risk of adverse child outcomes. However, to date, there is limited research exploring the role and relative contribution of modifiable and nonmodifiable risk factors in parents of children with a disability. The present study aimed to explore the role of various modifiable and nonmodifiable parenting, family and sociodemographic factors associated with the use of coercive parenting practices in parents of children with a disability. Methods: Caregivers ( N = 1392) enrolled in the Mental Health of Young People with Developmental Disabilities (MHYPeDD) programme in Australia completed a cross‐sectional survey about their parenting and their child aged 2–12 years with a disability. Measures covered a range of domains including relevant demographic and family background, use of coercive parenting practices, intensity of child behavioural difficulties and questions relating to parent and family functioning such as parental self‐efficacy, adjustment difficulties and quality of family relationships. Results: Parents of older children, those who were younger at the birth of their child, and parents who were co‐parenting or working reported more use of coercive parenting practices. Greater intensity of child difficulties, poorer parental self‐efficacy and parent–child relationships, and more parental adjustment difficulties were also significantly associated with more use of coercive parenting. Examination of the relative contribution of variables revealed parent–child relationship was a key contributing factor, followed by intensity of child behaviour problems, parent adjustment and parent confidence. Conclusions: These findings highlight a range of factors that should be targeted and modified through upstream prevention programmes and further inform our understanding of how coercive practices may be influenced through targeted parenting interventions.